Potential and weak links in the management of tuberculosis by Pakistani private pharmacy staff - Balquis, Fatima; Sohail, Muhammad Farhan; Hamid, Huma; Ullah, Waseem; Khan, Amer Hayat; Shahnaz, Gul (Frontiers in Public Health, 2023)
The emergence of multi-drug-resistant Tuberculosis (MDR-TB) is a global threat and an obstacle for effective control of Tuberculosis (TB) in Pakistan. Lack of proper TB knowledge of the staff in private pharmacies and sale of compromised quality anti-TB drugs are the main instigators of MDR-TB. Thus, the study was aimed at investigating the quality and storage conditions of fixed dose combination (FDCs) anti-TB drugs along with the awareness of staff working in private pharmacies regarding identification of potential TB patients and dispensing inappropriate treatment regimens contributing in MDR-TB. Results revealed the presence of pharmacists only at 11.5% pharmacies. About 81% staff at pharmacies had no awareness about MDR-TB while 89% pharmacies had no TB related informative materials. Staff identified that most of the TB patients (70%) were of poor socio-economic class which restricted their purchase of 4-FDCs only up to 2- 3 months. Only 23% were acquainted with Pakistan national TB program (NTP). Except for MDRTB, results showed significant correlation between experiences of staff with TB awareness. Findings from the quality evaluation of 4-FDCs-TB drugs indicated that the dissolution and content assay of rifampicin was not according to the specifications and overall 30% samples failed to comply with specifications. However, the other quality attributes were within limits. Thus, in conclusion, the data suggested that the private pharmacies could play a pivotal role in efficient management of NTP by timely identification of TB patents coupled with proper disease and therapy related education and counseling along with proper storage and stock maintenance